Water flow control and monitoring system in pipes using water flow sensor - Umar, Saidina; Basrah Pulungan, Ali; Habibullah; Dewi, Citra (Department of Electrical Engineering Universitas Negeri Padang, 2025)
This paper discusses the design, construction, and testing of a water flow control and monitoring system in pipes that aims to detect leaks and combine water flow in real time to improve efficiency and reduce potential losses due to leaks. This system is designed using water flow sensors placed in each channel in a certain number to detect the air flow rate. The difference in air flow read from several sensors is used as an indication of a leak. This system is integrated with a microcontroller and is equipped with control via an electric solenoid valve that allows for leak handling and air flow diversion when needed. Several tests have been conducted to ensure the system is ready for use, and the results show that the system is able to control air flow well without any problems, and is able to monitor air flow in real time, detecting changes in flow when a leak occurs. This research contributes to a device for controlling and monitoring water flow in pipes to improve the efficiency of water channel handling